Bimodal pattern of killing of DNA-repair-defective or anoxically grown Escherichia coli by hydrogen peroxide. - Imlay, J A (1986)
Two modes of killing of Escherichia coli K-12 by hydrogen peroxide can be distinguished. Mode-one killing was maximal with hydrogen peroxide at a concentration of 1 to 2 mM. At higher concentrations the killing rate was approximately half maximal and was independent of H2O2 concentration but first order with respect to exposure time. Mode-one killing required active metabolism during the H2O2 challenge, and it resulted in sfiA-independent filamentation of both cells which survived and those which were killed by the challenge. This mode of killing was enhanced in xth, polA, recA, and recB strains and was accelerated in all strains by an unidentified, anoxia-induced cell function. A strain carrying both xth and recA mutations appeared to undergo spontaneous mode-one killing only under aerobic conditions. Mode-one killing appeared to result from DNA damage which normally occurs at a low, nonlethal level during aerobic growth. Mode-two killing occurred at higher doses of H2O2 and exhibited a multihit dependence on both H2O2 concentration and exposure time. Mode-two killing did not require active metabolism, and killed cells did not filament, although survivors demonstrated a dose-dependent growth lag. Strains with DNA-repair defects were not especially susceptible to mode-two killing.